Optimizing Island Refuges against global Catastrophic and Existential Biological Threats: Priorities and Preparations. Issue 12 (22nd April 2021) - Boyd, Matt; Wilson, Nick
Abstract: Human civilization is vulnerable to global catastrophic biological threats and existential threats. Policy to mitigate the impact of major biological threats should consider worst‐case scenarios. We aimed to strengthen existing research on island refuges as a mitigating mechanism against such threats by considering five additional factors as well as recent literature on catastrophic risks and resilience. We also analyzed the performance of potential refuge islands during early phases the COVID‐19 pandemic. Using a composite indicator (scored from 0–1) based on 14 global macroindices, we present analysis supporting Australia (0.71), New Zealand (0.64), and Iceland (0.58) as the leading candidate island nation refuges to safeguard the survival of humanity and a flourishing technological civilization from the threat of a catastrophic pandemic. Data from the COVID‐19 pandemic supports this finding where islands have performed relatively well. We discuss the persisting weaknesses of even the best candidate refuges and the growing literature describing what preparations such a refuge should ensure to enhance resilience. Refuge preparations by Australia and New Zealand, in particular, may additionally provide some immunity against winter‐inducing catastrophes such as global nuclear war. Existing disaster resilience frameworks such as the Sendai framework could be worded to mandate preventive measures against global catastrophic and existential threats. The issue of island refuges against certain global catastrophic risks should be raised at relevant international political summits.